2001
DOI: 10.1073/pnas.141543298
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase ( Cyp19 ) expression is up-regulated by targeted disruption of Dax1

Abstract: DAX-1 [dosage-sensitive sex reversal, adrenal hypoplasia congenita (AHC) critical region on the X chromosome, gene 1] is an orphan nuclear receptor that represses transcription by steroidogenic factor-1 (SF-1), a factor that regulates expression of multiple steroidogenic enzymes and other genes involved in reproduction. Mutations in the human DAX1 gene (also known as AHC) cause the X-linked syndrome AHC, a disorder that is associated with hypogonadotropic hypogonadism also. Characterization of Dax1-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 61 publications
3
92
2
Order By: Relevance
“…SF-1-mediated P450arom expression. (18) Gurates et al also demonstrated that DAX-1 inhibits Ad4BP/SF-1-pathwaydependent P450arom expression in cultured human endometriotic glandular and endometrial stromal cells. (19) These in vitro studies clearly demonstrated the potentially pivotal roles of DAX-1 in the regulation of in situ steroidogenesis and steroid metabolism in human endometrium and its disorders, possibly through the inhibition of in situ steroid production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…SF-1-mediated P450arom expression. (18) Gurates et al also demonstrated that DAX-1 inhibits Ad4BP/SF-1-pathwaydependent P450arom expression in cultured human endometriotic glandular and endometrial stromal cells. (19) These in vitro studies clearly demonstrated the potentially pivotal roles of DAX-1 in the regulation of in situ steroidogenesis and steroid metabolism in human endometrium and its disorders, possibly through the inhibition of in situ steroid production.…”
Section: Discussionmentioning
confidence: 95%
“…(13) DAX-1 has also been demonstrated to repress Ad4BP/SF-1-mediated transactivation of other steroidogenic genes, (14,15) including genes for P450c17 and aromatase p450 (P450arom). (16)(17)(18) DAX-1 inhibits Ad4BP/SF-1 pathway-dependent P450arom expression in cultured human endometriotic and endometrial stromal cells. (19) In addition, DAX-1 interacts with both subtypes of estrogen receptors, ERγ and ERβ.…”
mentioning
confidence: 99%
“…This observation may reflect sexually dimorphic actions of ␤-catenin, or the fact that luteinizing hormone (rather than FSH) is the primary regulator of STAR in GCs (43). Dax1, a putative ␤-catenin target (30), can also selectively modulate Cyp19a1 over other steroidogenic enzymes (44). Thus, ␤-catenin signaling may contribute to differential production of estrogen and progesterone by gonadotropins during the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…To extend on this, another orphan member of the nuclear receptor family, Dax-1, exhibits an inhibitory effect on PII aromatase gene expression in normal settings however in the absence of Dax-1 in rats, Leydig cell tumors develop and a concomitant increase in aromatase gene expression results. 117 The precise extracellular regulator(s) that lead to the interaction of orphan transcription factors to the SPRE remain unknown however two have been postulated: (1) IGF-1: can regulate aromatase gene by stimulating SF-1 binding to the SFRE on PII in rat Leydig cell tumors 106 and (2) TH/TH-receptor complex is able to compete with SF-1 in binding to the SFRE response element on PII in rats. 107 The second is cyclic AMP responsive element (CRE) 112,113 which contains 3 CRE-like sequences (position -335: TGA ACT CA, position -231: TGA AAT CA and position -169: TGC ACG Figure 1.…”
Section: Molecular Mechanisms Controlling Aromatase Gene Expression Imentioning
confidence: 99%